An Evolutionary Narrative of Popular Music Learning Cultures:: A Case Study of the United Kingdom - Hueyuen, Choong (Malaysian Journal of Music, 2022)
For a very long time, popular music learning cultures had been characterised as informal and aural traditions. However, literature on the ways popular musicians learnt have documented increasing instances of popular musicians engaging with formal and non-aural modes of learning as time went by. Using the United Kingdom (UK) as a case study, the aim of this article is to establish an evolutionary narrative of how popular musicians learn. It begins with a chronological review of literature that examined the learning experiences of popular musicians between the 1970s and 2010s, and then discusses some observations regarding provisions of higher popular music education. In doing so, it revealed how the formalisation of popular music learning and technological advancements propelled the processes of becoming popular musicians in the UK to expand beyond features of informal learning and playing by ear. It argues that popular music learning cultures today comprise diverse combinations of formal and informal learning modes, notation- and ear-based practices, and resources made available by technological advancements, and thus, the informal and aural narrative pinned onto popular music learning cultures needs to be re-examined. Finally, it hopes to encourage discourses surrounding the learning of popular music to evolve beyond the issues of informal and aural-based learning and allocate more attention towards other means of learning in popular music.